2015
DOI: 10.1001/jamaneurol.2014.3739
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Elderly Patients With Glioblastoma

Abstract: IMPORTANCE Despite improvements in survival with aggressive chemoradiation, outcomes for patients diagnosed as having glioblastoma multiforme (GBM) remain poor. Survival is further limited in elderly patients, who are often unable to tolerate multimodality therapy. The appropriate treatment approach for elderly patients (aged >65 years) with GBM remains unclear. While the literature supports the use of standard radiotherapy (60 Gy), several recent studies have suggested that treatment with temozolomide monothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Although treatment for GBM patients has evolved, many of the trials leading to today’s standard of care initially excluded patients in their 60's and 70's [10]. Today’s standard of care remains maximum safe tumor resection, standard course RT of 60 Gy in 30 daily fractions over six weeks, and concurrent and adjuvant TMZ chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment for GBM patients has evolved, many of the trials leading to today’s standard of care initially excluded patients in their 60's and 70's [10]. Today’s standard of care remains maximum safe tumor resection, standard course RT of 60 Gy in 30 daily fractions over six weeks, and concurrent and adjuvant TMZ chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…That shorter os is likely multifactorial and reflects differing tumour biology in elderly patients, as well as differences in treatment patterns and tolerance of therapy [6][7][8] . Many elderly or frail patients are unable to tolerate combined chemoradiotherapy, and toxicities-including severe fatigue, myelosuppression, and infections-are common 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, chemotherapy with TMZ alone is put forth as an acceptable alternative to RT in elderly patients with GBM [32,33,34,35]. The NOA trial examined and compared patients who received TMZ-alone ( n = 195) versus RT-alone ( n = 178) for malignant astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al [32] also demonstrated the non-inferiority of TMZ to RT-alone in improving the overall survival in elderly, however at an increased risk of grade 3-4 toxicities. Zarnett et al [33], in their systematic review, concluded that elderly patients with MGMT promoter methylation are more likely to receive the greatest benefit from TMZ-alone regimen over RT. Metcalfe et al [36] in a retrospective cohort analysis study showed that the addition of adjuvant TMZ followed by concurrent TMZ with RT improves the overall survival in patients with newly diagnosed GBM who are 70 years or above.…”
Section: Discussionmentioning
confidence: 99%